Circadian changes and sex-related differences in fetal heart rate parameters - Kapaya, Habiba; Broughton Pipkin, Fiona; Hayes-Gill, Barrie; Loughna, Pamela V. (Springer Nature, 2016)
BACKGROUND: Previous researchers have studied circadian changes in the fetal heart rate (FHR) on small sample sizes and in a strictly controlled environment. This study was undertaken to investigate these changes during the late second and third trimesters, using a portable fetal electrocardiogram recording device (Monica AN24) in pregnant women in home and hospital environments with unrestricted mobility. METHODS: This was a prospective cohort study of 54 pregnant women with uncomplicated singleton pregnancies between 25 and 40 weeks gestation. FHR recordings were made up to 16 h at home or in the hospital setting in the United Kingdom. FHR data over 90 min periods were averaged and the day (7:00 am-11:00 pm) and night (11:00 pm-7:00 am) data from the same individual were compared. Data were examined for evidence of sex-related differences. RESULTS: During the night, there was a significant reduction in basal heart rate (bFHR) and a significant increase in short term variation (STV) and long term variation (LTV) (P < 0.05). Basal FHR decreased (P < 0.002), whereas LTV increased (P = 0.014) with advancing gestation. Male fetuses showed greater day: night variation than females regardless of gestation (P = 0.014). There was a higher bFHR in fetuses monitored during the day in hospital (P = 0.04). CONCLUSION: This study demonstrates that there are sex-, environment and time-related differences in the FHR parameters measured. These differences may need to be considered taken when interpreting FHR data.